HIF1 and ID1 Interplay Confers Adaptive Survival to HIF1α-Inhibition - Geng, Hao; Ko, Hyun-Kyung; Pittsenbarger, Janet; Harvey, Christopher T.; Xue, Changhui; Liu, Qiong; Wiens, Sadie; Kachhap, Sushant K.; Beer, Tomasz M.; Qian, David Z. (Frontiers in Cell and Developmental Biology, 2021)
Hypoxia is a universal pathological feature of solid tumors. Hypoxic tumor cells acquire metastatic and lethal phenotypes primarily through the activities of hypoxia-inducible factor 1 alpha (HIF1α). Therefore, HIF1α is considered as a promising therapeutic target. To date, while several HIF1α inhibitors have been discovered and validated in preclinical studies, the clinical translations of these agents have been less successful. The robust antitumor effects seen in preclinical models are not observed in clinical trials. The reasons for the poor clinical efficacy are unclear. We report that oncogenic protein ID1 is degraded in hypoxia via HIF1α -dependent mechanisms. When HIF1α is inhibited by shRNA or pharmacological inhibitors, ID1 protein is rescued. ID1 then supports tumor growth in hypoxia in vitro and in xenografts in vivo, conferring adaptive survival response and resistance to HIF1α -inhibitions. Mechanistically, ID1 compensates the loss of HIF1α by the upregulation of GLS2 and glutamine metabolism, thereby switching the metabolic dependency of HIF1α -inhibited cells from glucose to glutamine.